Leben bewahren – Sterben zulassen: Weltreligionen und Euthanasie - Heller, Birgit (Zeitschrift für Religionswissenschaft, 2001)
Today, most people live in pluralistic societies. Nevertheless, proponents of Christianity and Judaism are predominantly engaged in the current debate on euthanasia. But, looking round the world religions, it becomes obvious that discussions have already been started all over the world. The religious traditions accentuate different aspects and give impulses or even challenge the contemporary dealing with dying and death. All the different world religions ascribe a high value to life, which has to be protected and preserved. Therefore, active euthanasia is either totally rejected or – under certain strictly defined circumstances – very cautiously considered and partly admitted. There are considerable differences concerning the views on the due forms of passive euthanasia. Anyhow, the religious traditions provide different contexts for medical, ethical and juridical acting depending on special world-views. World-views, which give specific answers to the meaning of human life and death.